1977
DOI: 10.1099/0022-1317-36-1-123
|View full text |Cite
|
Sign up to set email alerts
|

Simian Virus 40 -- Chinese Hamster Kidney Cell Interaction. III. Characteristics of Chemical Induction in a Clone of Virogenic Transformed Cells

Abstract: SUMMARYA number of chemical and physical agents were screened to determine their effectiveness in inducing simian virus (SV4o) production in a virogenic clone of SV4o-transformed Chinese hamster cells. Mitomycin C (MC) was the most effective inducing agent, and MC induction was further characterized. It was found that levels of infectious SV4o DNA were increased above control levels as early as 6 h after addition of MC to the culture medium and reached maximum levels by 48 h. Virus capsid (V) antigen and virio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…This enhancement was observed reproducibly when u.v.-irradiation was performed at various times (o to 24 h) after infection. However, the degree of stimulation of SV4o production did not exceed io-fold in 4 independent experiments (not shown), which is significantly less than that usually observed upon MC treatment; this difference is in agreement with the relative inducing efficiency of these two agents on SV4o-transformed Chinese hamster cells (Morris et al 1977).…”
Section: Effect Of Caffeine On S V4o Replication In Chk CL I O Cellssupporting
confidence: 66%
See 4 more Smart Citations
“…This enhancement was observed reproducibly when u.v.-irradiation was performed at various times (o to 24 h) after infection. However, the degree of stimulation of SV4o production did not exceed io-fold in 4 independent experiments (not shown), which is significantly less than that usually observed upon MC treatment; this difference is in agreement with the relative inducing efficiency of these two agents on SV4o-transformed Chinese hamster cells (Morris et al 1977).…”
Section: Effect Of Caffeine On S V4o Replication In Chk CL I O Cellssupporting
confidence: 66%
“…In the present work, we have shown that MC, one of the most powerful inducers of polyoma and SV4o in cells transformed by these viruses (Fogel, 1972;Kaplan et al 1975;Morris et al 1977) is also capable of stimulating virus multiplication in Chinese hamster kidney cells infected with SV4o. A I o-to Ioo-fold increase in infectious virus production was reproducibly observed upon MC treatment of CHK Cl.lo cells infected with SV4 o DNA.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations